2017
DOI: 10.1002/14651858.cd006580.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Culture-specific programs for children and adults from minority groups who have asthma

Abstract: The available evidence showed that culture-specific education programmes for adults and children from minority groups are likely effective in improving asthma-related outcomes. This review was limited by few studies and evidence of very low to low quality. Not all asthma-related outcomes improved with culture-specific programs for both adults and children. Nevertheless, while modified culture-specific education programs are usually more time intensive, the findings of this review suggest using culture-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(34 citation statements)
references
References 89 publications
1
32
0
Order By: Relevance
“…Therefore, we developed one to meet the different needs in our study population. 12 In our study, KAP of asthma patients was assessed using a modified form of validated KAP questionnaire which is reliable and culture fair to our geographic area. This study shows that patients with asthma still lack adequate knowledge about the disease and have many misconceptions regarding the illness and its treatment, which needs to be rectified.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we developed one to meet the different needs in our study population. 12 In our study, KAP of asthma patients was assessed using a modified form of validated KAP questionnaire which is reliable and culture fair to our geographic area. This study shows that patients with asthma still lack adequate knowledge about the disease and have many misconceptions regarding the illness and its treatment, which needs to be rectified.…”
Section: Discussionmentioning
confidence: 99%
“…However, cultural competency was helpful at the individual level and in specific racial and ethnic groups (Baily et al, 2009;Hawthorne, Robles, Cannings-John, & Edwards, 2008;McCallum, Morris, Brown, & Chang, 2017). Studies grounded in cultural competence demonstrated positive results in nurse practitioner training (Debiasi & Selleck, 2017).…”
Section: Previous Frameworkmentioning
confidence: 99%
“…There are multiple explanations to the underuse of controller medications in disadvantaged asthma patients including limited access to care, cultural beliefs, inadequate health literacy, and disparities in prescribing patterns leading to suboptimal quality of care [75]. Despite these barriers, using a culturally sensitive approach through asthma education programs targeting disadvantaged asthma patients, multiple pediatric programs have successfully improved adherence to preventive therapies and improved asthma outcomes [84]. Identifying reasons for suboptimal adherence, such as fear of adverse effects, fear of addiction, cost, inconvenience or complexity of treatment regimens can lead to an individualized conversation, education and medication regimen changes that can improve adherence in the disadvantaged asthma patient [85].…”
Section: Management Strategy Summary For the Disadvantaged Asthma Phementioning
confidence: 99%